A system for determining human engagement behavior. - Sheikh Said, Normahdiah (2009)

(untitled)
This invention is a system to determine human engagement behavior when interacting with a multimedia design system based on design features which exploit psychological needs. The X-factor is an indicator matrixes that will determine the level of engagement an end-user will encounter as they interact with interactive design features which exploit psychological needs found in courseware or systems designed for them. This matrix is useful for pre and post designing process and also useful during a designing process.